Obsidian from the northern sector of the Main Ethiopian Rift: implications for archeology. (6th April 2021) - Negash, Agazi; Alene, Mulugeta; Asrat, Asfawossen; Nash, Barbara
ABSTRACT: Obsidian is abundant in the Main Ethiopian Rift (MER). Petrological and geochemical features of obsidian from four volcanic centers in the MER, namely Birenti, Dofen, Fentale and Kone, are presented. Compositional and petrological variability is noted among the Dofen and Fentale obsidian, but not in those from Kone and Birenti where each have separate but uniform elemental composition. The Fentale and Kone obsidian were source materials for the artifacts of a number of Middle Stone Age and Later Stone Age/Neolithic sites in the region. We have yet to determine whether Dofen and Birenti were sources for archeological artifacts. The study also shows that volcanic episodes from a single center do not necessarily result in compositional variability.